Foamable polyolefin compositions providing increased flexibility
By using citric acid or expandable polymer microspheres as foamable polymer compositions in the cable sheath layer as foaming agent, the problem of balance between flexibility and tensile properties of the cable sheath material is solved, and the resistance to breaking is improved and reduces costs.
Patent Information
- Application Number
- CN202411248494.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-06
- Filing Date
- 2020-03-05
- Publication Date
- 2024-12-13
Smart Images

Figure BDA0005031576250000171 
Figure BDA0005031576250000191 
Figure BDA0005031576250000201
Abstract
Description
[0001] This application is a divisional application of the PCT national phase application in China with an application date of March 5, 2020, a date of entry into the Chinese national phase of September 2, 2021, an application number of 202080018290.6 (international application number is PCT / EP2020 / 055825), and an invention name of “Foamable polyolefin composition providing increased flexibility”. Technical Field
[0002] The present invention relates to a foamable polymer composition comprising a polyolefin polymer and a foaming agent, and a foamed polymer composition obtained by foaming the foamable polymer composition. Further, the present invention relates to the use of the foamable composition or the foamed polymer composition for producing a cable layer and a cable comprising at least one layer, the layer comprising the foamable polymer composition or the foamed polymer composition. Background Art
[0003] In wire and cable (W&C) applications, a typical cable comprises a conductor surrounded by one or more layers of polymer material. The cable is usually produced by extruding layers onto the conductor.
[0004] Power cable is defined as a cable for transmitting energy working at any voltage level. The voltage applied to the power cable can be alternating current (AC), direct current (DC) or transient (pulse). In addition, power cables are typically represented according to their operating voltage level, such as low voltage (LV), medium voltage (MV), high voltage (HV) or extra high voltage (EHV) power cables, and these terms are well known. Power cable is defined as a cable for transmitting energy working at any voltage level, typically working at a voltage higher than 100V. LV power cables typically work at a voltage lower than 3kV. MV and HV power cables work at higher voltage levels. Typical MV power cables usually work at a voltage of 3kV to 36kV, and typical HV power cables work at a voltage higher than 36kV. LV power cables usually include electrical conductors, insulation layers and outer sheaths. Typically, MV power cables include conductors surrounded by an inner semiconductive layer, an insulation layer, an outer semiconductive layer and an outer sheath in the order described.
[0005] In addition, there is usually a metal shield between the cable sheath and the outer semi-conductive layer for MV power cables (above 6kV), and between the cable sheath and the insulation for LV power cables (1kV to 3kV). This metal shield is grounded. The metal shield keeps the electromagnetic field inside the power cable and protects the power cable insulation by keeping the potential of the outer semi-conductive layer or insulator constant. In most cables, this metal shield consists of copper wire, but it can also be made of aluminum or copper tape. The size thickness of the copper wire is specific and designed for the worst case scenario, such as when a lightning strike occurs or an electrical breakdown occurs in the cable, when high currents will be generated in the metal shield. The thickness of the copper wire is specific so that the temperature of the metal shield should have a good margin and not exceed the melting point of the sheath.
[0006] A typical cable usually comprises a conductor surrounded by one or more layers (depending on the field of application). For example, a power cable has several layers of polymer material, including an inner semiconducting layer, then an insulating layer, then an outer semiconducting layer. One or more further auxiliary layers may be added to these layers. An outer protective polymer layer is known, in particular, as a sheath layer.
[0007] Safety, reliability and long service life are important key factors required in cable applications. Since the outer sheath layer provides the outer protection of the cable, it plays an important role in providing system functionality.
[0008] In addition, the cable industry requires flexible cables that are easy to install. Furthermore, when the cables are installed in power stations, there are also particularly high requirements for the flexibility of power cables.
[0009] Low density polyethylene (LDPE), for example produced in a high pressure process, is commonly used for all types of cable layers, including the sheath layer. Its disadvantage is that its mechanical properties are not satisfactory for the requirements of a protective sheath layer.
[0010] Linear low density polyethylene (LLDPE) is known, in particular as a jacket layer material. However, typically, LLDPE also does not fully satisfy the mechanical properties required of a polymer in a cable layer, such as a jacket layer.
[0011] The mechanical properties of the layer can be improved by increasing the density of polyethylene. High-density polyethylene (HDPE) polymers do provide improved mechanical strength, such as abrasion resistance, for cable layers in particular. However, the disadvantage of HDPE is that the stress cracking resistance is limited (expressed as, for example, ESCR), and the flexibility required for the jacket layer in particular is low. Non-flame retardant jackets are an integral part of all application areas, and the jacket materials are generally based on PVC or PE. PE resins have been used for a long time in different cable jacket applications due to their good barrier properties and mechanical properties. In power cables, HDPE or MDPE are the main materials used due to the demand for high temperature resistance, high abrasion resistance and mechanical strength. In particular, bimodal HDPE materials provide a good combination of properties. In traditional external multi-pair and coaxial telecommunication cables, although HDPE and MDPE are also used, LDPE has been largely replaced by a tougher, low-shrinkage material, LLDPE. In optical fiber cables, LLDPE or MDPE are generally used for long truck networks, while for access networks, HDPE is generally used as a jacket material in particular. In small cable constructions, flexible LLDPE, LDPE or copolymer grades are used. In general, multimodal PE is superior to unimodal PE from a processability and mechanical properties point of view.
[0012] In order to be properly installed with simple and quick operations, the cable needs to be particularly flexible so that it can be inserted into wall channels and / or wall conduits and follow the bends of the installation path without being damaged. It is also desirable for the cable to have enhanced flexibility while still having the toughness and abrasion resistance required for demanding installation conditions. When installing the cables, they may be pulled into grooves, which requires the jacket material to have special toughness to avoid being damaged during installation. Reducing the weight of the cable and increasing its flexibility can reduce damage to the cable due to tearing or scraping actions during customer installation, but toughness is still required. In addition, the flexibility of the cable can be increased by manufacturing the cable with an expanded jacket instead of a solid jacket, which has favorable results during the installation of the cable.
[0013] It is thus known that by foaming, the flexibility of the layer material increases. However, it is also known that expansion reduces the toughness and thus will reduce the tensile properties, such as the breaking stress.
[0014] The foaming of the polyolefin composition can be carried out using a chemical foaming agent, a physical foaming agent or expandable polymer microspheres or a combination thereof. A chemical foaming agent is a substance that releases a foaming gas by a thermal decomposition reaction, and the chemical foaming agent is consumed in the foaming reaction. Examples of such substances are hydrazine, hydrazide or azodicarbonamide, or those based on a combination of a solid organic acid (or its metal salt) and one or more alkali metal carbonates or one or more alkali metal bicarbonates, such as a combination of citric acid / citric acid derivatives and sodium bicarbonate.
[0015] Physical foaming agents are gases that are injected directly into the polymer melt. In such processes, chemical foaming agents are usually used as cell nucleating agents because the gas formed by the reaction of the foaming agent acts as a nucleation point and the energy of bubble formation is low. The gas used as a physical foaming agent can be, for example, N 2 or CO 2 Both chemical and physical foaming extrusion processes are used for the extrusion of foamed telecommunication cable insulation. In chemical foaming, all of the foaming gas comes from the decomposition of the chemical foaming agent.
[0016] The expandable microspheres are characterized by having a polymer wall that surrounds one or more pockets or particles of a blowing agent or propellant within the microsphere. The polymer wall may have reactive functional groups on its surface to provide a fusible microsphere. When the microspheres are heated, they expand to form micro hollow spheres (microballoons) containing a polymer shell.
[0017] Foamable polyolefin compositions are described, for example, in WO 2018 / 049555 A1, EP 1 243 957 A2 or WO 2017 / 102341.
[0018] It is generally desirable to obtain as large an expansion as possible while still achieving the desired mechanical properties; in particular, a higher expansion will reduce material costs by increasing the space occupied by the voids. In addition to occupying more space through the voids, the sheath is better able to absorb forces applied to the cable from the outside. The increased flexibility as described provides a cable that is easier to install, but tensile properties are also important. More specifically, it is expected that the breaking stress preferably meets the limits set by international standards IEC60501-1 and IEC60502-2 for power cables with extruded insulation, with accessories rated at 1 kV to 30 kV and cables rated at 6 kV to 30 kV.
[0019] It is therefore important to find a balance between flexibility (which is improved by foaming the layer material) and acceptable stretch properties (which are deteriorated by foaming).
[0020] Another aspect is that conventional sheath materials are linear polymers with low melt strength. Melt strength is required so that the cells can grow without breaking during the foaming process. Summary of the invention
[0021] An object of the present invention is to provide a foamable or foamed polymer composition that overcomes the above problems. Therefore, an object of the present invention is to provide a foamable or foamed polymer composition with a balance of flexibility and tensile properties. The foamable composition or foamed polymer composition can be used for cable layers, preferably for sheath layers.
[0022] Another object of the present invention is to provide a cable comprising at least one layer comprising a foamable polymer composition or a foamed polymer composition. DETAILED DESCRIPTION
[0023] The present invention is based on the surprising finding that all of the above objects can be achieved by using a blowing agent comprising citric acid and / or citric acid derivatives or expandable polymer microspheres in a foamable polymer composition.
[0024] Therefore, in a first aspect, the present invention provides a foamable polymer composition comprising
[0025] (A) a polyolefin polymer having no silane moieties and comprising 20 wt % to 99.99 wt % of a linear low density polyethylene, and
[0026] (B) a blowing agent in an amount of 0.01 wt% to 3 wt% based on the total foamable polymer composition, wherein the blowing agent consists of citric acid and / or a citric acid derivative.
[0027] In a second aspect, the present invention provides a foamable polymer composition comprising
[0028] (A) a polyolefin polymer, and
[0029] (B) a blowing agent in an amount of 0.01 wt % to 3 wt % based on the total foamable polymer composition, wherein the blowing agent consists of expandable polymer microspheres,
[0030] And the composition does not contain fluororesin.
[0031] The invention further provides a foamed polymer composition obtained by foaming the foamable polymer composition according to the first and second aspects.The foamable composition according to the first and second aspects or the respective foamed polymer composition may be used in a cable layer, preferably in a sheath layer.
[0032] There is further provided a cable comprising at least one layer comprising the foamable polymer composition or foamed polymer composition according to the first and second aspects.
[0033] The foamable or foamable composition of the present invention can produce a layer for a cable with a balance of flexibility and tensile properties. Therefore, the foamable or foamable composition as described herein makes the flexible cable easy to install. Further, the foamable or foamable composition also provides increased fracture resistance (e.g., during ploughing into the cable during installation), because the cable of the present invention has increased flexibility and still has good fracture resistance, thereby being less likely to be damaged by, for example, hard and / or sharp rocks. In addition, the cable sheath composition of the present invention can make the cable cost lower and more sustainable, because less material is needed in the layer of the cable.
[0034] The present invention uses citric acid and / or citric acid derivatives in a first aspect, or expandable polymer microspheres in a second aspect as a foaming agent. Generally, a foaming agent is a substance that is capable of producing a porous structure in a foamable polymer composition through a foaming process. The foaming agent is typically used when the polymer is molten. The porous structure in the polymer matrix reduces the density of the foamable polymer composition. Flexibility is mainly affected by density.
[0035] Citric acid is an endothermic foaming agent. "Exothermic foaming agent" herein refers to a compound or mixture of compounds that is thermally unstable and decomposes within a certain temperature interval to produce gas and heat. Further, "endothermic foaming agent" herein refers to a compound or mixture of compounds that is thermally unstable and causes heat absorption when generating gas within a certain temperature interval.
[0036] This endothermic blowing agent is easier to control because the reaction requires a continuous supply of heat to continue. This also allows for better control of the gas release of the blowing agent, especially in continuous processes such as extrusion.
[0037] Another advantage of citric acid or citric acid derivatives is that they release CO during decomposition. 2 As the main blowing gas. With N released from hydrazine, hydrazide or azodicarbonamide (ADCA) 2 In comparison, CO 2 Better solubility in foamable polymer compositions.
[0038] Citric acid and its derivatives decompose into water, carbon dioxide and solid decomposition products. The decomposition reaction is endothermic, which means that a continuous supply of heat energy is required for the decomposition reaction to occur. The temperature at which the decomposition reaction occurs rapidly depends on the chemical (citric acid or citric acid derivative), but is generally around 200°C. The decomposition temperature of citric acid and citric acid derivatives is well above the melting point of polyolefin polymers and can therefore be compounded into polyolefin polymers prior to cable extrusion without the need for pre-decomposition in the mixing step.
[0039] In a first aspect, the blowing agent consists of citric acid and / or its derivatives. The advantage of using only "one" blowing agent (B) is an even better control of the foaming process, since only one decomposition temperature interval has to be considered during processing, which reduces the complexity of the process.
[0040] In the first aspect wherein the blowing agent consists of citric acid and / or its derivatives, the amount of blowing agent (B) is preferably 0.02 wt% to 2.0 wt%, more preferably 0.05 wt% to 1.0 wt%, most preferably 0.1 wt% to 0.5 wt%, based on the total foamable polymer composition.
[0041] Preferably, the citric acid derivative comprises an alkali metal salt of citric acid, an ester of citric acid or a mixture thereof. The alkali metal salt of citric acid preferably comprises one or more selected from the group consisting of monosodium citrate, disodium citrate, trisodium citrate, monopotassium citrate, dipotassium citrate and tripotassium citrate.
[0042] In the first aspect in which the blowing agent is citric acid and / or its derivatives and / or mixtures, the foamable polymer composition preferably further comprises a mineral nucleating agent (C). The mineral nucleating agent (C) is typically a high surface area mineral. The interface between the mineral nucleating agent (C) and the polymer composition melt will serve as a nucleation point for bubble formation during the foaming process because the energy required for bubble formation in the interface is lower than the energy required in the bulk polymer melt. The mineral nucleating agent (C) preferably comprises a magnesium-containing compound, a calcium-containing compound, a silicon-containing compound or a mixture thereof. The mineral nucleating agent (C) can be any mineral filler, such as silicon dioxide, talc, calcium carbonate, kaolin, dolomite, zeolite, mica wollastonite or a clay mineral.
[0043] In order to obtain a high and uniform distribution of the mineral nucleating agent (C) in the foamable polymer composition, the mineral nucleating agent (C) is added to the foamable polymer composition, preferably compounded or melt-mixed with the foamable polymer composition. The mineral nucleating agent (C) is preferably in powder form, i.e. in the form of small particles. The average particle size is usually in the order of 0.1 μm to 50 μm.
[0044] Preferably, a foaming agent masterbatch (BAMB) comprising citric acid and / or its derivatives and a mineral nucleating agent (C) as described above is used. The foaming agent masterbatch may further comprise a polymer carrier, such as a polyethylene carrier. More preferably, the foaming agent masterbatch consists of the foaming agent (B) and the nucleating agent (C) and the polymer carrier. The foaming agent masterbatch is added to the foamable polymer composition, preferably compounded or melt-mixed with the foamable polymer composition.
[0045] Preferably, the distribution of citric acid and / or its derivatives in the polymer composition is improved by melt mixing the foaming agent masterbatch into the foamable polymer composition by compounding before the foamable polymer composition is extruded in the extruder. Since the gas released from the decomposition of citric acid and / or its derivatives is better distributed in the polyolefin polymer melt, this leads to improved cell structure. For communication cables, it is crucial to have a good cell structure in the foamed insulator to have isotropic electrical properties. It is desirable to have a cell structure with multiple small cells evenly distributed in the insulator. The cell structure is also important for mechanical properties. Compared with a structure with unevenly distributed larger cells (because this will produce weak parts in the insulator), having multiple well-distributed small cells will provide better compression resistance.
[0046] In a second aspect, the blowing agent (B) consists of expandable polymer microspheres. When mixed in the product and heated to cause expansion within the matrix, the expandable polymer microspheres can act as a blowing agent. Similarly, for expandable polymer microspheres, it is also easy to control the expansion by continuously supplying heat to the reaction.
[0047] As described in US 3615972, expandable polymer microspheres are adapted to expand when heated. These microspheres are monocellular particles comprising a body of resin material encapsulating a volatile fluid. When heated, the resin material of the thermoplastic microspheres softens and the volatile material expands, resulting in a significant increase in the size of the entire microsphere. When cooled, the resin material in the microsphere shell stops flowing and tends to maintain its enlarged size, and the volatile fluid in the microsphere tends to condense, resulting in a decrease in pressure in the microsphere. Another advantage of these expandable polymer microspheres is that they do not release any gas.
[0048] Typically, expandable polymer microspheres are made of a thermoplastic polymer shell, such as methyl methacrylate and acrylonitrile, methyl methacrylate, acrylonitrile and vinylidene chloride, o-chlorostyrene, p-tert-butylstyrene, vinyl acetate and copolymers thereof, i.e. styrene-methacrylic acid, styrene-acrylonitrile, styrene-methyl methacrylate. The gas in the shell may be an aliphatic hydrocarbon gas, such as isobutylene, pentane or isooctane. These microspheres are available in a variety of sizes and forms, with expansion temperatures typically ranging from 80°C to 130°C. Expandable polymer microspheres are available, for example, from Akzo Nobel under the trademark EXPANCEL TM and from Henkel under the trademark DUALITE TM Commercially available. The term "expandable microsphere" as used in this disclosure is intended to encompass any hollow elastic container filled with a volatile fluid suitable for expansion. The microsphere is typically a spherical particle, but may also have other shapes, such as tubular, ellipsoidal, cubic, granular, etc., all of which are suitable for expansion when exposed to an energy source.
[0049] In the second aspect in which the blowing agent (B) consists of expandable polymer microspheres, the composition does not contain a fluororesin. A fluororesin is a resin containing fluorine-carbon bonds, such as polytetrafluoroethylene (PTFE). Moreover, also for this aspect, the advantage of using only "one" blowing agent (B) is that the foaming process can be even better controlled, since only one temperature interval has to be considered during processing, which reduces the complexity of the process.
[0050] In the second aspect in which the blowing agent (B) consists of expandable polymer microspheres, the amount of blowing agent is preferably 0.02 wt% to 2 wt%, more preferably 0.05 wt% to 1 wt%, most preferably 0.1 wt% to 0.5 wt%, based on the total weight of the foamable polymer composition.
[0051] The expandable polymer microspheres are preferably compounded or melt mixed with the foamable polymer composition. Preferably, a blowing agent masterbatch (BAMB) is used, which comprises expandable polymer microspheres and a carrier resin such as a copolymer of ethylene vinyl acetate. Preferably, the blowing agent masterbatch comprises 80 wt % to 20 wt % of expandable polymer microspheres, more preferably 70 wt % to 60 wt % of expandable polymer microspheres. More preferably, the blowing agent masterbatch consists of the blowing agent (B) and the polymer carrier resin.
[0052] The blowing agent masterbatch is added to the foamable polymer composition, preferably compounded or melt mixed with the foamable polymer composition. Also for expandable polymer microspheres, the distribution in the polymer composition is improved by melt mixing the blowing agent masterbatch into the foamable polymer composition by compounding, preferably before the foamable polymer composition is extruded in an extruder.
[0053] In the first aspect, the polyolefin polymer (A) does not have a silane moiety and comprises a linear low density polyethylene (LLDPE) of at least 20 wt % to 99.99 wt % based on the gross weight of the foamable composition. In the second aspect, the polyolefin polymer (A) preferably does not have a silane moiety and comprises a linear low density polyethylene of at least 20 wt % to 99.99 wt % based on the gross weight of the foamable composition. Therefore, in the first aspect and also preferably in the second aspect, the present invention uses a polyolefin polymer that should not be crosslinked and therefore does not have a silane moiety. Therefore, it is not necessary to introduce the silane moiety into the polyolefin polymer. Crosslinking can be used to increase branching, thereby increasing melt strength.
[0054] Melt strength is required for chemical foaming and physical foaming. Specifically, in the first aspect in which citric acid and / or its derivatives are used as a foaming agent, in order to foam the polyolefin polymer composition, the polyolefin polymer composition must have good melt strength without crosslinking, because poor melt strength will cause the cell structure to collapse, which is not good for the mechanical properties or electrical properties of the cable layer. However, for expandable microspheres, the microsphere polymer shell will prevent the bubble from rupturing, so melt strength is not necessary.
[0055] However, for both aspects, the MFR of the polyolefin polymer (A) is measured according to ISO 1133 at 190°C and 2.16 kg load. 2 Preferably, it is 0.1 g / 10min to 10 g / 10min, more preferably 0.2 g / 10min to 5 g / 10min. This MFR range is also preferred from a processing perspective, because lower MFR polymers will be very viscous and difficult to foam. Too high MFR materials are not preferred because the melt strength of the polymer decreases with increasing MFR, and good melt strength is important for the foaming process.
[0056] Polyethylene density is commonly used to classify different types of polyethylene - HDPE, MDPE, LLDPE, LDPE, VLDPE and ULDPE. The density of polyethylene is directly related to the crystallinity of the material and therefore to the melting point, as the melting point is essentially determined by the lamellar thickness of the crystalline part. The density of pure linear PE with high crystallinity is typically 960 kg / m 3 Up to 970kg / m 3 , i.e. about 965kg / m 3 , the melting point is typically 125° C. to 135° C., ie, about 130° C. As the density of polyethylene decreases, the melting point decreases.
[0057] The density of the polyolefin polymer (A) in both aspects is preferably 880 kg / m 3 Up to 950kg / m 3 , more preferably 890kg / m 3 Up to 940kg / m 3 , most preferably 900kg / m 3 Up to 930kg / m 3 .
[0058] Furthermore, the following preferred aspects also apply to the first and second aspects of the present invention.
[0059] The polyolefin polymer (A) of the foamable polymer composition preferably comprises 50 to 99 wt%, more preferably 70 to 95 wt%, most preferably 80 to 90 wt% of linear low density polyethylene, based on the total weight of the foamable composition.
[0060] Linear low density polyethylene (LLDPE) is a homopolymer or a copolymer. Homopolymer refers to linear low density polyethylene (LLDPE), which comprises at least 90% by weight of ethylene monomer, preferably at least 95% by weight of ethylene monomer, most preferably at least 99% by weight of ethylene monomer, respectively. If linear low density polyethylene (LLDPE) is a copolymer, the copolymer comprises ethylene monomer and one or more comonomers. The comonomer can be an alpha-olefin with 3 to 12 carbon atoms, such as propylene, butene, hexene, octene, decene. Preferably, linear low density polyethylene (LLDPE) is a copolymer. More preferably, linear low density polyethylene (LLDPE) is a copolymer of ethylene and butene.
[0061] Preferably, the MFR of LLDPE 2 It is 0.1 g / 10 min to 10 g / 10 min, more preferably 0.2 g / 10 min to 5.0 g / 10 min, most preferably 0.5 g / 10 min to 2.0 g / 10 min.
[0062] Preferably, the density of LLDPE is 880 kg / m 3 Up to 930kg / m 3 , more preferably 910kg / m 3 Up to 925kg / m 3 , more preferably 917kg / m 3 Up to 923kg / m 3 .
[0063] Linear low density polyethylene (LLDPE) polymers are polymerized in a low pressure process and are, for example, LLDPE homopolymers or LLDPE copolymers of ethylene and one or more comonomers as described above. Further, LLDPE is polymerized in a low pressure polymerization process in the presence of a catalyst. The catalyst may be, for example, a Phillips catalyst, a metallocene catalyst or a Ziegler-Natta catalyst. A Phillips catalyst is preferred. The polymerization may be, for example, gas phase polymerization, slurry polymerization or a combination of slurry polymerization / gas phase polymerization or a combination of gas phase polymerization / gas phase polymerization. The polymerization may also be a solution polymerization.
[0064] Polymerization can be carried out in one reactor or in several reactors connected in series, giving unimodal, bimodal or multimodal polyethylene. The "morphology" of a polymer refers to the structure of its molecular weight distribution, i.e. the appearance of a curve showing the number of molecules as a function of molecular weight. A polymer is called "unimodal" if the curve exhibits one maximum, while it is called "bimodal", "multimodal", etc. if the curve exhibits one very broad maximum or two or more maxima and the polymer consists of two or more fractions. For example, if a polymer is produced in a continuous multistage process, using reactors connected in series and using different conditions in each reactor, the polymer fractions produced in the different reactors will each have their own molecular weight distribution and weight average molecular weight. When recording the molecular weight distribution curve of such a polymer, the individual curves of these fractions are superimposed into the molecular weight distribution curve of the total resulting polymer product, usually resulting in a curve with two or more distinct maxima.
[0065] In the production of unimodal polyethylene, ethylene polymers are produced in a reactor under certain conditions regarding monomer composition, hydrogen pressure, temperature, pressure, etc. In the copolymerization of ethylene, other olefins having up to 12 carbon atoms are usually used as comonomers, for example α-olefins having 3 to 12 carbon atoms, such as propylene, butene, 4-methyl-1-pentene, hexene, octene, decene, etc.
[0066] In the production of bimodal polyethylene, for example, a first ethylene polymer is produced in a first reactor under certain conditions of monomer composition, hydrogen pressure, temperature, pressure, etc. After polymerization in the first reactor, the reaction mixture comprising the produced polymer is fed into a second reactor, where further polymerization is carried out under other conditions. Typically, a comonomer is added moderately or in small quantities in the first reactor or is not added at all, producing a first polymer with a high melt flow rate (low molecular weight), whereas more comonomer is added in the second reactor to produce a second polymer with a low melt flow rate (high molecular weight). In the copolymerization of ethylene, other olefins with a maximum of 12 carbon atoms are typically used as comonomers, for example, alpha-olefins with 3-12 carbon atoms, such as propylene, butene, 4-methyl-1-pentene, hexene, octene, decene, etc. The resulting final product is composed of an intimate mixture of polymers from two reactors, and the different molecular weight distribution curves of these polymers together form a molecular weight distribution curve with a wide maximum or two maximum values, i.e., the final product is a bimodal polymer mixture. Linear low density polyethylene is preferably unimodal.
[0067] As mentioned above, in order to foam, the polyolefin polymer composition must have good melt strength. Melt strength increases with the increase of long chain branching in the polymer. Therefore, linear polymers such as LLDPE and HDPE generally have poor melt strength. It is preferred to improve the melt strength by incorporating LDPE into the foamable polyolefin polymer composition and to ensure that the foamed layer has a closed cell structure and uniform cell distribution.
[0068] Preferably, based on the total weight of the foamable polymer composition, the polyolefin polymer (A) further comprises 0.1 wt % to 80 wt %, more preferably 1 wt % to 60 wt %, more preferably 5 wt % to 40 wt % of low density polyethylene, and most preferably 10 wt % to 20 wt % of low density polyethylene.
[0069] Low density polyethylene (LDPE) is a homopolymer or a copolymer. More preferably, low density polyethylene (LDPE) is a homopolymer. Homopolymers are preferred because the main reason for adding LDPE to a blend is to improve melt strength, and this property stems from the long chain branching structure of LDPE, regardless of the comonomer.
[0070] Preferably, the MFR of LDPE 2 It is 0.1 g / 10 min to 10 g / 10 min, more preferably 0.2 g / 10 min to 5.0 g / 10 min, most preferably 1.0 g / 10 min to 3.0 g / 10 min.
[0071] Preferably, the density of LDPE is 880 kg / m 3 Up to 930kg / m 3 , more preferably 910kg / m 3 Up to 927kg / m 3 , more preferably 920kg / m 3 Up to 925kg / m 3 .
[0072] Low density polyethylene (LDPE) polymer is polymerized in a high pressure free radical polymerization process, possibly in the presence of one or more comonomers. Further, LDPE is polymerized in a high pressure polymerization process in the presence of one or more initiators and optionally a chain transfer agent (to control MFR).
[0073] LDPE can be produced, for example, in a tubular polymerisation reactor or in an autoclave polymerisation reactor, suitably in a tubular polymerisation reactor.
[0074] Preferably, the polyolefin polymer (A) without silane moieties comprises 20 wt % to 99.99 wt % of linear low density polyethylene and 0.1 wt % to 80 wt % of low density polyethylene, more preferably 50 wt % to 99 wt % of linear low density polyethylene and 1 wt % to 60 wt % of low density polyethylene, more preferably 70 wt % to 95 wt % of linear low density polyethylene and 5 wt % to 40 wt % of low density polyethylene, most preferably 80 wt % to 90 wt % of linear low density polyethylene and 10 wt % to 20 wt % of low density polyethylene, based on the total weight of the foamable polymer composition.
[0075] Preferably, the composition comprises a polyolefin polymer (A) and a blowing agent (B) in an amount of 0.01 wt % to 3.0 wt %, the polyolefin polymer (A) not carrying a silane moiety and comprising 20 wt % to 99.99 wt % of a linear low density polyethylene and 0.1 wt % to 80 wt % of a low density polyethylene, wherein the blowing agent consists of citric acid and / or a citric acid derivative or mixture, or consists of expandable polymer microspheres; more preferably 50 wt % to 99 wt % of a linear low density polyethylene and 1 wt % to 60 wt % of a low density polyethylene. , and the blowing agent (B) in an amount of 0.02 wt% to 2.0 wt%; more preferably 70 wt% to 95 wt% of the linear low density polyethylene and 5 wt% to 40 wt% of the low density polyethylene, and the blowing agent (B) in an amount of 0.05 wt% to 1.0 wt%; most preferably 80 wt% to 90 wt% of the linear low density polyethylene and 10 wt% to 20 wt% of the low density polyethylene, and the blowing agent (B) in an amount of 0.1 wt% to 0.5 wt%, all based on the total weight of the foamable polymer composition.
[0076] Preferably, the foamable polymer composition comprises at least 90 wt% polyolefin.Preferably, all polymers in the polymer composition comprise only polyethylene.
[0077] Preferably, in the first aspect also similarly to the second aspect, the foamable polymer composition does not contain a fluororesin. Preferably, in both aspects, the foamable polymer composition does not contain an azo compound and / or a physical foaming agent.
[0078] The azo compound is azodicarbonamide, azobisisobutyronitrile or diazoaminobenzene.
[0079] Physical blowing agents are gases injected directly into the extrusion barrel under high pressure. Such gases are, for example, nitrogen, carbon dioxide, air and low boiling hydrocarbons such as propane and butane.
[0080] Therefore, the present invention has the advantage that the foamable polymer composition of the present invention can be foamed into a foamed polymer composition without using a toxic foaming agent (such as an azo compound, a fluororesin) and a physical foaming agent.
[0081] More preferably, in both aspects, the foamable polymer composition does not comprise any further blowing agent.
[0082] The foamable polymer composition preferably comprises an antioxidant. The antioxidant is preferably a phenolic antioxidant, a phosphorus-containing antioxidant or a blend thereof. The phenolic antioxidant is preferably a blend of pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (CAS No. 6683-19-8; commercially available from BASF under the trade name Irganox 1010) and tris-(2,4-di-tert-butylphenyl)phosphite (CAS No. 31570-04-4; commercially available from BASF under the trade name Irgafos 168). This antioxidant blend is commercially available from BASF as Irganox B561.
[0083] The antioxidant is preferably present in an amount of 0.01 to 2 wt%, more preferably 0.04 to 1 wt%, and most preferably 0.06 to 0.5 wt%, based on the total foamable polymer composition.
[0084] The foamable polymer composition preferably comprises an acid scavenger. The acid scavenger is preferably calcium stearate, sodium stearate, zinc stearate or a mixture thereof, more preferably calcium stearate.
[0085] The amount of the acid scavenger is preferably 0.01 to 2.0 wt%, more preferably 0.02 to 1.0 wt%, and most preferably 0.04 to 0.5 wt%, based on the total foamable polymer composition.
[0086] The foamed polymer composition can be obtained by foaming the foamable polymer composition according to the present invention.
[0087] The foaming is carried out by heating the foamable polymer composition to a temperature of preferably 150° C. to 240° C., more preferably 180° C. to 235° C., and even more preferably 210° C. to 230° C. Within this temperature range, the blowing agent (B) present in the foamable polymer composition, in the case of citric acid or a citric acid derivative, thermally decomposes into a gaseous product as described above, or in the case of microspheres, the resin material of the thermoplastic microspheres as described above softens and the volatile material expands, thereby producing a foamed polymer composition.
[0088] The foaming process includes mixing and homogenizing the components in the first part of the extruder, and then optimizing the foaming properties (e.g., the degree of foaming and the cell structure, size and distribution in the cable layer) in the end of the extruder, the die and the extruder head outlet. In addition, the process steps for making the foaming composition and the cable layer can include any common extruder, such as a single screw extruder.
[0089] The degree of foaming can be controlled by varying extrusion parameters such as adjusting the temperature settings of the extruder and / or extruder head, line speed, screw speed, extruder die position, cooling bath position, and cooling water temperature.
[0090] The flexural modulus of the foamed polymer composition is preferably from 10 MPa to 300 MPa, more preferably from 50 MPa to 250 MPa, most preferably greater than 100 MPa and less than 219 MPa when measured according to ISO 178. The flexural modulus of the foamed polymer composition is preferably at least 10 MPa when measured according to ISO 178.
[0091] The expansion degree of the foamed polymer composition is preferably from 2% to 30%, more preferably from 3% to 20%, more preferably from 4% to 17%, most preferably from 5% to 13.7%.
[0092] "Grossness" (G) is defined as:
[0093] G=(d 0 / d e -1)×100
[0094] where d 0 represents the density of the unexpanded polymer, d e The measured apparent density or unit volume weight of the expanded polymer (in g / cm 3 count).
[0095] The foamed polymer composition preferably has a stress at break measured according to ISO 527-1 and ISO 527-2 of 12.5 to 50 MPa, more preferably 13 to 40 MPa, still more preferably 14 to 30 MPa, most preferably at least 14 to 20 MPa.
[0096] The strain at break of the foamed polymer composition, measured according to ISO 527-1 and ISO 527-2, is preferably from 400% to 1500%, more preferably from 500% to 1000%, most preferably from 550% to 790%.
[0097] The invention further relates to the use of the foamable or foamed polymer composition for producing a cable layer.Preferably, the foamable or foamed polymer composition is used for producing a sheathing layer.
[0098] The invention further relates to a cable comprising the foamable polymer composition or the foamed polymer composition. More preferably, the cable comprises at least one layer comprising the foamable polymer composition or the foamed polymer composition. The cable may be a power cable, such as an LV, MV or HV cable, such as an LV or MV cable, such as an LV cable; or may be a communications cable.
[0099] Preferably, the cable comprises a conductor surrounded by one or more layers, wherein at least one layer comprises a foamable or foamed polyethylene polymer composition.Preferably, the jacket layer comprises a foamable or foamed polymer composition.
[0100] In a first example of a method for manufacturing a power cable or a communication cable, a polyolefin material and a blowing agent and possible further additives are suitably combined by compounding in a conventional manner (e.g. by extruding with a screw extruder or a kneader). The molten mixture of the obtained polyolefin polymer and the blowing agent can then be suitably granulated. In addition, the pellets obtained can be of any size and shape.
[0101] This can be carried out in the cable production line, for example, in a mixer before the cable extruder or in the cable extruder, or in both. The obtained mixture is used to form a cable layer. The method for manufacturing a power cable or a communication cable comprises extruding the provided foamable composition onto a cable core to form a cable sheath.
[0102] According to the method for manufacturing a power cable or a communication cable as described herein, a suitable method comprises the step of applying (e.g. by coextrusion) one or more layers on the conductor, wherein at least one layer, i.e. the outer protective layer (sheath), comprises, e.g. consists of, a foamable composition comprising a polyolefin material and a blowing agent, wherein the composition will comprise from 0.01% to 3.0% by weight of a blowing agent relative to the total weight of the polymer composition.
[0103] The term "coextrusion" means in this article that in the case of two or more layers, the layers can be extruded in separate steps, or at least two or all of the layers can be coextruded in the same extrusion step, as is known in the art. The term "coextrusion" also means in this article that one or more extrusion heads are used to form all or part of a layer or multiple layers at the same time. For example, triple extrusion can be used to form three layers. If more than one extrusion head is used to form the layers, for example, two extrusion heads can be used to extrude the layers, the first extrusion head is used to form the inner semiconductive layer and the inner part of the insulating layer, and the second head is used to form the outer insulating layer and the outer semiconductive layer. Coextrusion can be carried out in any conventional cable extruder, such as a single screw or twin screw extruder.
[0104] As is known, a melt mixture of a foamable polymer composition or its components can be applied to form a layer. Melt mixing means mixing above the melting point of at least the main polymer component of the obtained mixture, and for example, but not limited to, mixing at a temperature of at least 15° C. above the melting point or softening point of one or more polymer components. Melt mixing can be carried out in a cable extruder or a mixer, such as a kneader, before the extruder, or in both.
[0105] Further, the method for manufacturing a power cable or a communication cable comprises foaming the cable jacket, which occurs when the melt of the provided blend leaves the cable extruder, because this causes a pressure drop, since the atmospheric pressure is lower than the pressure in the extruder. When the melt pressure is reduced to atmospheric pressure, the gas formed in the extruder by the blowing agent citric acid or its derivatives will no longer dissolve in the melt. Instead, the gas will form bubbles, i.e., cells, in the polymer melt, and the bubbles will continue to grow until the melt is cooled to a temperature at which the melt viscosity is too high to allow further growth of the cells. The resulting cable jacket is foamed, which means that it contains dispersed bubbles, i.e., cells.
[0106] Example
[0107] 1. Measurement method
[0108] Melt flow rate
[0109] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the melt viscosity of a polymer. The MFR of PE is determined at 190°C and the MFR of PP is determined at 230°C. The load at which the melt flow rate is determined is usually indicated by a subscript, e.g. MFR 2 It is measured under 2.16kg load (condition D), MFR 5 It is measured under 5kg load (condition T), or MFR 21 Measured under 21.6 kg load (condition G).
[0110] density
[0111] The density of polyolefin polymers is measured according to ISO 1183-1 method A on samples prepared according to ISO 17855.
[0112] Flexural modulus
[0113] Flexural modulus was determined according to ISO 178:2010. The test specimens were 2 mm thick extruded tapes. The span length between the supports was 64 mm, the test speed was 2 mm / min, the load cell was 100 N. The equipment used was an Alwetron TCT 10. The samples were conditioned for at least 16 hours at 23 + / - 2 °C and 50% relative humidity before testing.
[0114] Tensile test according to EN60811-100
[0115] Fracture stress and fracture strain
[0116] The stress and strain at break were measured according to ISO 527-1:2012 at 23°C and 50% relative humidity on an Alwetron TCT 10 tensile tester at a speed of 25 mm / min. The extensometer used was an MFE-900. The test specimens were 2 mm thick extruded tapes. The specimens were conditioned at 23 + / - 2°C and 50% relative humidity for at least 16 hours before testing. The average values of 6-10 specimens are reported herein.
[0117] Expansion
[0118] The density of the pellets is measured using a scale with density measurement, and then the density of the ribbon is measured using the same technique. The expansion is the difference in density between the pellets and the ribbon.
[0119]
[0120] in
[0121] d pl : Density of the belt, in kg / m 3 count
[0122] d pe : Density of the particle, in kg / m 3 count
[0123] 2. Materials
[0124] LLDPE: Unimodal chromium-catalyzed LLDPE copolymer with butene as comonomer, MFR 2 The viscosity is 0.85g / 10min and the density is 920kg / m 3 .
[0125] LDPE:MFR 2 The carbon content is 2.0g / 10min and the density is 923kg / m 3 Tubular LDPE homopolymer.
[0126] PO 2217: An endothermic blowing agent masterbatch commercially available from Tramaco GmbH, containing a citric acid derivative, wherein the amount of the citric acid derivative is 100% by weight of the added blowing agent. The masterbatch further comprises a mineral nucleating agent and a polymer carrier.
[0127] Expancel 980MB 120: An exothermic blowing agent masterbatch commercially available from Akzo Nobel containing 65 wt% expandable polymer microspheres and 35 wt% of a carrier resin which is a copolymer of ethylene vinyl acetate (EVA).
[0128] Irganox 1010: pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate, commercially available from BASF GmbH (CAS No.: 6683-19-8).
[0129] Irgafos 168: tris-(2,4-di-tert-butylphenyl)phosphite, stabilizer, commercially available from BASF GmbH (CAS number: 31570-04-4).
[0130] Calcium stearate
[0131] 3. Preparation of Examples
[0132] Before testing, the composition according to Table 1 was the blowing agent used in the inventive examples, compounded on a BUSS MDK46 continuous extruder (built in 1985) using a BUSS AG co-kneader. The line is a single screw kneader with a screw diameter of 46 mm and 11 L / D. Compounding is a melt mixing of polymers, wherein one or more polymers and / or additives are mixed in a molten state. It is generally used for dispersion and distribution of additives and fillers in a polymer melt.
[0133] For the inventive examples, the foaming agent masterbatch Expancell 980MB 120 or Tracel PO 2217 was mixed into the polyolefin containing LLDPE and LDPE during the compounding process. By using a mixture containing polyolefin materials, a blend for producing exemplary foaming tape samples was obtained. The composition was then extruded into a 2 mm thick tape on a Collin extruder Teach-Line E 20T with a 2 mm slit die and a screw speed of 55 rpm. After leaving the die, the tape was cooled on a roller. The temperature settings are as follows, and the amount of the foaming agent masterbatch Expancell 980MB 120 or the foaming agent masterbatch Tracel PO 2217 for each sample can be seen in Table 1.
[0134] T1:50 / 170 / 210 / 210 / 210 / 210
[0135] T2:50 / 170 / 220 / 220 / 220 / 220
[0136] T3:50 / 170 / 230 / 230 / 230 / 230
[0137] Comparative Example CE1 was produced in the same manner, except that no blowing agent was added to the polyolefin material.
[0138] Table 1: All values are in wt %.
[0139]
[0140] 4. Results
[0141] Table 2:
[0142]
[0143] Two different blowing agents, Expancell 980MB 120 and Tracel PO 2217, have been tested. Expancell 980MB 120 was used in two different amounts. In addition, different extrusion temperature settings with maximum temperatures of 210°C, 220°C and 230°C were tested. It can be seen that the higher the expansion, the lower the flexural modulus, indicating increased flexibility, and the lower the breaking stress and breaking strain, indicating poorer tensile properties. However, it was surprisingly found that the improved flexibility indicated by the lower flexural modulus values of the inventive examples can be obtained while the breaking stress and breaking strain remain acceptable.
Claims
1. A foamable polymer composition comprising (A) a polyolefin polymer having no silane moiety and comprising 20 wt % to 99.99 wt % of a linear low density polyethylene and further comprising 0.1 wt % to 80 wt % of a low density polyethylene, based on the total weight of the foamable polymer composition, and (B) a blowing agent in an amount of 0.01 wt% to 3 wt% based on the total foamable polymer composition, wherein the blowing agent consists of citric acid and / or a citric acid derivative.
2. A foamable polymer composition comprising (A) a polyolefin polymer having no silane moieties and comprising 20 wt % to 99.99 wt % of a linear low density polyethylene, and (B) a blowing agent in an amount of 0.01 wt % to 3 wt % based on the total foamable polymer composition, wherein the blowing agent consists of expandable polymer microspheres, And the composition does not contain fluororesin.
3. The foamable polymer composition of claim 1, wherein the citric acid derivative comprises an alkali metal salt of citric acid, an ester of citric acid, or a mixture thereof.
4. The foamable polymer composition according to claim 3, wherein the alkali metal salt of citric acid comprises one or more selected from the group consisting of monosodium citrate, disodium citrate, trisodium citrate, monopotassium citrate, dipotassium citrate and tripotassium citrate.
5. The foamable polymer composition according to any one of the preceding claims, wherein the polyolefin polymer (A) has an MFR2 of from 0.1 g / 10 min to 10 g / 10 min, measured according to ISO 1133 at 190°C and 2.16 kg load.
6. A foamable polymer composition according to any one of the preceding claims, wherein the density of the polyolefin polymer (A) is 880 g / m 2 measured according to ISO 1183-1 on a sample prepared according to ISO 1872-2. 3 Up to 950g / m 3 .
7. The foamable polymer composition according to any one of the preceding claims, wherein the polyolefin polymer (A) further comprises 0.1 wt% to 80 wt% of a low density polyethylene, based on the total weight of the foamable polymer composition.
8. A foamable polymer composition according to any one of the preceding claims, wherein the composition does not comprise an azo compound and / or a physical blowing agent.
9. The foamable polymer composition according to any one of the preceding claims, wherein the foamable polymer composition comprises an antioxidant and / or an acid scavenger, preferably the antioxidant is a phenolic antioxidant, a phosphorus-containing antioxidant or a mixture thereof, preferably the acid scavenger is calcium stearate, sodium stearate, zinc stearate or a mixture thereof, more preferably calcium stearate.
10. Foamed polymer composition obtained by foaming the foamable polymer composition according to any one of the preceding claims.
11. The foamable polymer composition according to claim 10, wherein foaming is performed by heating the foamable polymer composition to a temperature of 150°C to 240°C.
12. A foamed polymer composition according to any one of claims 10 or 11, wherein the foamed polymer composition has a flexural modulus of 10 MPa to 300 MPa when measured according to ISO 178, or a degree of expansion of 2% to 30% or a stress at break of 12.5 MPa to 50 MPa when measured according to ISO 527-1 and ISO 527-2; or a strain at break of 400% to 1500% when measured according to ISO 527-1 and ISO 527-2.
13. Use of the foamable composition according to claims 1 to 9 or the foamed polymer composition according to claims 10 to 12 for producing a cable layer, preferably a sheathing layer.
14. A cable comprising at least one layer comprising the foamable polymer composition according to claims 1 to 9 or the foamed polymer composition according to claims 10 to 12, preferably the layer is a sheathing layer.
Citation Information
Patent Citations
Coated central strength member for fiber optic cables with reduced shrinkage
EP1243957A2
Expansible thermoplastic polymer particles containing volatile fluid foaming agent and method of foaming the same
US3615972A
Cable comprising a foamed layer comprising a polyolefin polymer and a blowing agent
WO2017102341A1
Nucleating agent for foamable cable insulation
WO2018049555A1
